Political Communication Strategy in Legislative Elections: A Case Study of Nasrul in the Period of 2019-2024 in Payakumbuh City - Muhammad Danil; Erliza Fitri (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2021)
This study discusses the political communication carried out by Nasrul in the 2019–2024 legislative elections in Payakumbuh City. The focus of this research is on the elected candidates from the Prosperous Justice Party (PKS) due to being elected as a member of the DPRD Payakumbuh City with the most votes. The author assumes that his victory was motivated by good political communication. This research is a field research with a qualitative approach, while data collection is carried out through interviews with direct respondents Nasrul as the main source and secondary sources are the head of the PKS faction, a team of volunteers, community leaders who were selected based on sampling. The purpose of this study was to